2006
DOI: 10.1016/j.wasman.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of enhanced methane oxidation in compost: Temperature and moisture response

Abstract: Landfilling is one of the most common ways of municipal solid waste disposal. Degradation of organic waste produces CH(4) and other landfill gases that significantly contribute to global warming. However, before entering the atmosphere, part of the produced CH(4) can be oxidised while passing through the landfill cover. In the present study, the oxidation rate of CH(4) was studied with various types of compost as possible landfill cover. The influence of incubation time, moisture content and temperature on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 36 publications
2
61
0
Order By: Relevance
“…There are several reasons for the discrepancy found between the theoretically expected higher methane turnover rates when oxygen was available (here in winter in Holzsee) and the detected minimal potential rates. Of course, the constant incubation temperature of 8°C used in rates determination throughout the year did not mimic in situ conditions and probably influenced the rates recorded (Höfle 1979, Glissmann et al 2004, Mor et al 2006. Besides temperature, under field conditions, MOB may have been limited due to decreased substrate (CH 4 ) availability (Segers 1998) or, for example, due to the presence of the competitive substrate ammonium (NH 4 + ), influencing CH 4 oxidation (Steudler et al 1989, King & Schnell 1994.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons for the discrepancy found between the theoretically expected higher methane turnover rates when oxygen was available (here in winter in Holzsee) and the detected minimal potential rates. Of course, the constant incubation temperature of 8°C used in rates determination throughout the year did not mimic in situ conditions and probably influenced the rates recorded (Höfle 1979, Glissmann et al 2004, Mor et al 2006. Besides temperature, under field conditions, MOB may have been limited due to decreased substrate (CH 4 ) availability (Segers 1998) or, for example, due to the presence of the competitive substrate ammonium (NH 4 + ), influencing CH 4 oxidation (Steudler et al 1989, King & Schnell 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Park et al (2005) concluded that moisture content is the most important factor controlling the CH 4 oxidation rate is a sandy soil landfill cover. Mor et al (2006) found that the effect of the soil moisture content on CH 4 oxidation in various types of compost was time-dependent and that the optimum moisture content ranges between 45 and 110% (dry weight basis).…”
Section: Moisture Contentmentioning
confidence: 99%
“…They also concluded that soil temperatures in excess of 30� C for long periods can lead to a reduction in CH 4 oxidation activity. Scheutz and Kjeldsen (2004) reported that CH 4 oxidation increased exponentially (with R 2 ¤0.91) with increases in soil temperature from 2 to 25� C. The maximum CH 4 oxidation rate occurred at 30� C, and the oxidation rate started to decline at 40� C. The effect of temperature on CH 4 oxidation in various types of compost was studied by Mor et al (2006), who found that the effect of temperature on CH 4 oxidation is time-dependent and that the optimum temperature range is between 15 to 30� C. Borken et al (2006) found that in forest soils, summer drought may increase CH 4 oxidation.…”
Section: Temperaturementioning
confidence: 99%
“…Methanotrophic community structure and activity differ with temperature (12,41,49) as well as with other environmental conditions, such as the concentrations of CH 4 and O 2 , pH, and nitrogen stress (27,61). Temperature also influences the enzymatic activity of methanotrophs, including hydroxypyruvate reductase, hexulose phosphate synthase, formate dehydrogenase, and ribulose bisphosphate carboxylase activities (45).…”
mentioning
confidence: 99%